2016
DOI: 10.1590/1518-8345.0723.2708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with preoperative anxiety in children aged 5-12 years

Abstract: Objective:to estimate the prevalence and factors associated with preoperative anxiety in children who wait for outpatient surgery. Method:cross-sectional analysis of baseline data of a prospective cohort study that investigates the predictors of postoperative pain in children aged 5-12 years submitted to inguinal and umbilical hernia repair. It was selected 210 children, which were interviewed in the preoperative holding area of a general hospital. Anxiety was evaluated using the modified Yale Preoperative Anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 31 publications
(52 reference statements)
1
37
0
8
Order By: Relevance
“…Power analysis was performed using G*Power 3.1.2 (Heinrich-Heine University, Düsseldorf, Germany). A previous study reported that the mean (SD) of m-YPAS score was 30.1 (8.4) in the control group undergoing elective surgery [ 17 ]. For clinical significance of the effect of the VR game, a reduction of 20% of the m-YPAS score was necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Power analysis was performed using G*Power 3.1.2 (Heinrich-Heine University, Düsseldorf, Germany). A previous study reported that the mean (SD) of m-YPAS score was 30.1 (8.4) in the control group undergoing elective surgery [ 17 ]. For clinical significance of the effect of the VR game, a reduction of 20% of the m-YPAS score was necessary.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome of this study was m‐YPAS score. A previous investigation reported that the mean(s.d.) m‐YPAS score of the control group was 30·1(8·4).…”
Section: Methodsmentioning
confidence: 99%
“…A previous investigation reported that the mean(s.d.) m‐YPAS score of the control group was 30·1(8·4). A decrease in m‐YPAS score of 20 per cent resulting from a VR tour was considered clinically significant.…”
Section: Methodsmentioning
confidence: 99%
“…Con frecuencia, en la literatura se evalúa el fenómeno de la ansiedad perioperatoria del paciente pediátrico desde la perspectiva de su prevalencia, la que se encuentra entre 42-70% (28,29) . Sin embargo, no se ha evaluado el fenómeno desde la prevalencia de las estrategias para evitarlo, en este caso desde el uso de ansiólisis perioperatoria con el fin de mitigar sus efectos.…”
Section: Wwwmedigraphicorgmx Discusiónunclassified